A morphology-based phylogenetic analysis of Fasciolariidae (Gastropoda: Buccinoidea) - Couto, Diogo R.; Simone, Luiz R. L. R. (Zootaxa, 2019)
Fasciolariids are buccinoid neogastropods and key predators in the tropics and subtropics, comprising more than 500 species in the subfamilies Fasciolariinae, Fusininae and Peristerniinae. Tulip shells, horse-conchs, spindles, etc., have been grouped into heterogeneous combinations of unrelated species, while several generic names have been used to group conchologically similar species. The latest molecular phylogenetic study conflicts with the current circumscription of many genera, and even more so, with the three currently recognized subfamilies. This work is the first morphological approach to the phylogeny of fasciolariids, using a parsimony analysis in TnT of 53 taxa based on 100 characters. This analysis reveals a monophyletic Fasciolariidae, with the genera Dolicholatirus and Teralatirus representing the most basal clade in the family, followed by three nodes that correspond to a fusinine grade, which includes the genus Pseudolatirus (Peristerniinae). A terminal clade groups the peristerniine genera Peristernia and Fusolatirus, fasciolariines and the remaining peristerniines. Although none of these clades correspond to currently accepted taxonomic groups, the latter two clades are corroborated in the most recent multilocus molecular phylogeny. This study supports the utility of morphological data in the recovery of groups, even in the molecular era.